Regulatory T Cells and Their Prognostic Relevance in Hematologic Malignancies - Giovanni D’Arena; Candida Vitale; Marta Coscia; Agostino Festa; Nicola Matteo Dario Di Minno; Vincenzo De Feo; Michele Caraglia; Gioacchino Calapai; Luca Laurenti; Pellegrino Musto; Giovanni Di Minno; Daniela Fenoglio (Journal of Immunology Research, 2017)
Regulatory T cells (Tregs) have a fundamental function in monitoring the immune homeostasis in healthy individuals. In cancer and, in particular, in hematological malignancies, Tregs exert a major immunosuppressive activity, thus playing a critical role in tumor cell growth, proliferation, and survival. Here, we summarize published data on the prognostic significance of Tregs in hematological malignancies and show that they are highly conflicting. The heterogeneity of the experimental approaches that were used explains—at least in part—the discordant results reported by different groups that have investigated the role of Tregs in cancer. In fact, different tissues have been studied (i.e., peripheral blood, bone marrow, and lymph node), applying different methods (i.e., flow cytometry versus immunohistochemistry, whole blood versus isolated peripheral blood mononuclear cells versus depletion of CD25+ cells, various panels of monoclonal antibodies, techniques of fixation and permeabilization, and gating strategies). This is of relevance in order to stress the need to apply standardized approaches in the study of Tregs in hematological malignancies and in cancer in general.